Ion-dipole model for electrolyte solutions: Application of the associative mean spherical approximation - Holovko, M.F.; Kapko, V.I. (Condensed Matter Physics, 2007)
The solution of the associative mean-spherical approximation for ion- dipolar system is reinvestigated and
expressed in terms of only five parameters. Three of them have counterparts in the case without association,
and the other two are the monomer fractions of ions and dipoles. The explicit expressions for the thermodynamic
quantities are represented in a simpler form. Numerical results for thermodynamic properties and
phase equilibria are presented. Розв’язок середньосферичного наближення представлено через п’ять параметрiв. Три з них аналогiчнi для безасоцiативного випадку, а два iнших є мономерними фракцiями iонiв та диполiв. Точнi вирази для термодинамiчних величин є представленi в простiй формi. Представленi чисельнi результати для термодинамiчних функцiй та фазової рiвноваги.